The Expertise Business Development Strategy of PT Prima Kelola IPB (Subsidiary Company of PT BLST Group) Through Business Model Canvas Approach - Kamil, Fathan; Satria, Arif; Zulbainarni, Nimmi (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: PT Prima Kelola IPB business application currently does not have an optimal business model so the right strategy is needed to develop the business model. Purpose: The objectives of this study are to analyze the current business model through a Business Model Canvas mapping (BMC) approach, determine three priority elements on BMC, compile an improvement business model canvas, and formulate alternative strategies to develop. Design/methodology/approach: The method used in this study is the Business Model Canvas approach, Importance Performance Analysis, and SWOT analysis. Findings/Result: The results of this study show that the three priority elements selected on BMC are customer segment, key activities, and key partnerships. Based on the results of SWOT analysis and FGD, the formulated alternative strategies are: 1) creating a strategic alliance for all IPB University in seeking projects; 2) expansion of collaboration with alumni network abroad to reach global markets; 3) optimizing the network by adding expertise, lecturers, practitioners, suppliers, other partners. Conclusion: The development of this business model is expected to be able to encourage the company's portfolio efforts to be maximized in increasing business volume, increasing operational efficiency, and increasing the market reach of PT Prima Kelola IPB through strategic steps that can be taken in this research.Originality/value (State of the art): This research contributes to the limited discourse in the literature on business development strategies of IPB University's subsidiaries by integrating SWOT and AHP methods to produce alternative strategies as a step for companies to develop new business models. Keywords: BMC, importance performance analysis, SWOT, alternative strategy, business model